2015
DOI: 10.3823/1780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Needle Stick Injuries And Their Underreporting Among Healthcare Workers In The Department Of Obstetrics And Gynaecology

Abstract: Introduction: Needle stick and sharp injuries (NSSIs) are hazardous and are frequently reported injuries among health care workers (HCW). These injuries expose them to infectious disease pathogens such as Hepatitis B, Hepatitis C and HIV that can be lethal. The physicians, nurses, medical students and other healthcare workers are highly susceptible to needle stick injuries. Standard precautions are available for all the workers and students' safety purposes. Every incident is compulsory to be reported but some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Medical students are a group of health care workers that are at high risk to get HBV and HCV infections because of their direct contact with patients, blood and other body fluids during their professional training, and lack of experience and professional skills increases the risk of infection in the course of invasive medical procedures [ 12 ]. Medical students receive percutanous injuries as often or more than health care workers and are, therefore, at greater risk of occupational exposure to HBV and HCV infections than health care workers, a fact that might partially be explained by poor knowledge and non-adherence to universal infection control procedures [ 13 , 14 ]. In addition to this, there exists a widely prevalent problem of underreporting of this risk exposures by students, which represents a missed opportunity for initiating post exposure prophylaxis, early detection of seroconversion and implementation of prevention strategies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students are a group of health care workers that are at high risk to get HBV and HCV infections because of their direct contact with patients, blood and other body fluids during their professional training, and lack of experience and professional skills increases the risk of infection in the course of invasive medical procedures [ 12 ]. Medical students receive percutanous injuries as often or more than health care workers and are, therefore, at greater risk of occupational exposure to HBV and HCV infections than health care workers, a fact that might partially be explained by poor knowledge and non-adherence to universal infection control procedures [ 13 , 14 ]. In addition to this, there exists a widely prevalent problem of underreporting of this risk exposures by students, which represents a missed opportunity for initiating post exposure prophylaxis, early detection of seroconversion and implementation of prevention strategies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that NSSIs is responsible for 37.6% of HCWs contracting HBV, 39% HCWs contracting HCV, and 4.4% HCWs contracting HIV infection [4]. Hepatitis B infection carry the greatest risk of transmission and health impact, with 37-62% of exposed HCWs eventually show sero-conversion and 22-31% in which hepatitis B infection clinically manifests [5].…”
Section: Introductionmentioning
confidence: 99%
“…In our study majority 21% had perceived that NSIs occurred due to their inattentiveness followed by 20% dueto procedures done in an emergency. Similarly NagandlaK et al [18] have reported that 52.6% of the NSIs occurred during emergency care procedures.…”
Section: Discussionmentioning
confidence: 89%